1994
DOI: 10.1111/j.1464-5491.1994.tb00240.x
|View full text |Cite
|
Sign up to set email alerts
|

An Audit of Cushioned Diabetic Footwear: Relation to Patient Compliance

Abstract: The recurrence rate of neuropathic foot ulcers is reported in 51 diabetic patients regularly attending a diabetic foot clinic. All of the patients were provided with protective footwear reducing peak plantar pressure at the forefoot area by 50% (versus normal shoes), and were followed up for up to 4 years. Compliance with this footwear was recorded by assessing the daily time of wearing protective or normal shoes, and compliance with foot care was recorded from the entries in the patients charts. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
0
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 5 publications
6
99
0
6
Order By: Relevance
“…Nevertheless, this type of shoe cannot completely reduce pressure in the ulcerated zone when the patient is walking or standing upright (13,14). It must be emphasized that the effectiveness of the shoe also depends on how long the patient wears it (15). Therefore, the effectiveness of this device is strictly related to patient compliance and the training and information given by the health care provider (16).…”
Section: Caravaggi and Associatesmentioning
confidence: 99%
“…Nevertheless, this type of shoe cannot completely reduce pressure in the ulcerated zone when the patient is walking or standing upright (13,14). It must be emphasized that the effectiveness of the shoe also depends on how long the patient wears it (15). Therefore, the effectiveness of this device is strictly related to patient compliance and the training and information given by the health care provider (16).…”
Section: Caravaggi and Associatesmentioning
confidence: 99%
“…Normal stresses originate by the repetitive vertical pressure on the foot while shear stresses occur when deep tissue slides under superficial tissue. It is currently accepted that reduction of abnormally high PPP during walking helps in the prevention and treatment of neuropathic ulcerations [2,3]. In this research study, total contact inserts (TCI) were used as the offloading mechanism because multiple studies have shown that the addition of a TCI can reduce PPP 16−48% under the metatarsal heads [4][5][6][7][8] compared to therapeutic footwear alone.…”
Section: Introductionmentioning
confidence: 99%
“…Chantelau et al (21,22) conducted two descriptive studies of therapeutic footwear as the primary intervention on patients with diabetic foot complications (a history of polyneuropathy, limb ischemia, foot ulceration, or prior forefoot or toe amputation) in a German population at moderate to high risk of reulceration. Both studies were assigned a II-3 study design rating because of their descriptive nature.…”
Section: Multifactoral Interventions Including Therapeutic Footwearmentioning
confidence: 99%
“…Chantelau's second descriptive study tracked 51 patients with a history of neuropathic foot ulcers, including some patients from the 1990 study, to assess the influence of patient's footwear adherence on reulceration risk (22). All 51 patients were provided custom shoes with plastazote, neoprene, and poron inserts (Fig.…”
Section: Multifactoral Interventions Including Therapeutic Footwearmentioning
confidence: 99%